CT perfusion for predicting intracranial atherosclerotic middle cerebral artery occlusion - Wang, Zigao; Yasheng, Abudoukeyoumu; Ling, Yifeng; Zhao, Hongchen; Mao, Yiting; Yang, Shilin; Cao, Wenjie (Frontiers in Neurology, 2024)
Backgrounds and Purpose: Identifying the underlying cause of acute middle cerebral artery occlusion (MCAO) as intracranial atherosclerotic stenosis (ICAS) or embolism is essential for determining the optimal treatment strategy before endovascular thrombectomy. We aimed to evaluate whether baseline computed tomography perfusion (CTP) characteristics could differentiate ICAS-related MCAO from embolic MCAO.We conducted a retrospective analysis of the clinical and baseline CTP data from patients who underwent endovascular thrombectomy for acute MCAO between January 2018 and December 2022. Core volume growth rate was defined as core volume on CTP divided by onset to CTP time. Multivariate logistic analysis was utilized to identify independent predictors for ICAS-related acute MCAO, and the diagnostic performance of these predictors was evaluated using receiver operating characteristic curve analysis.Results: Among the 97 patients included (median age, 71 years; 60% male), 31 (32%) were diagnosed with ICAS-related MCAO, and 66 (68%) had embolism-related MCAO. The ICAS group was younger (p = 0.002), had a higher proportion of males (p = 0.04) and smokers (p = 0.001), a lower prevalence of atrial fibrillation (AF) (p < 0.001), lower NIHSS score at admission (p = 0.04), smaller core volume (p < 0.001), slower core volume growth rate (p < 0.001), and more frequent core located deep in the brain (p < 0.001) compared to the embolism group. Multivariate logistic analysis identified core volume growth rate (aOR 0.46, 95% CI 0.26-0.83, p = 0.01) as an independent predictor of ICAS-related MCAO. A cutoff value of 2.5 ml/h for core volume growth rate in predicting ICAS-related MCAO was determined from the receiver operating characteristic curve analysis, with a sensitivity of 81%, specificity of 80%, positive predictive value of 66%, and negative predictive value of 90%.Slow core volume growth rate identified on baseline CTP can predict ICAS-related MCAO. Further prospective studies are warranted to confirm and validate these findings.